Bistatic SAR Image Formation: A Systematic Approach - Rodriguez-Cassola, Marc; Prats-Iraola, Pau; Krieger, Gerhard; Reigber, Andreas; Moreira, Alberto (IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2014)
In this paper, we provide a systematic overview on bistatic SAR image formation for arbitrary platform trajectories. Bistatic SAR may offer improved flexibility, performance and cost-efficiency if compared to monostatic SAR systems certainly at the expense of increased operational complexity. In the previous years, the road from experimental to operational bistatic radar systems has been paved with the launch of TanDEM-X [1], the first bistatic SAR in space. Future bistatic SAR systems will encompass multistatic constellations and formations with large baselines capable of delivering novel Earth observation products with improved performance and coverage. In this context, efficiency and accuracy in bistatic SAR image formation becomes an important challenge, asking for the development of suitable signal processing algorithms. This paper describes first the relevant developments on bistatic SAR image formation. The validity and shortcomings of previously suggested approaches for different bistatic geometries is systematically discussed. An overview on bistatic SAR image formation is provided, stressing those key techniques and algorithms which, in our opinion, are applicable in future operational systems and missions; the theoretical background is complemented by results from multiple pioneering airborne, spaceborne, and hybrid air-/spaceborne bistatic SAR experiments conducted at DLR over the past decade.
DLR Import::2019-04-03